Three individually addressable spin qubits in a single molecule - Borilovic, Ivana; Roubeau, Olivier; Le Guennic, Boris; van Slageren, Joris; Lenz, Samuel; Teat, Simon J; Aromí, Guillem (Chemical communications (Cambridge, England), 2022)
An asymmetric bis-phenol-β-diketone (H L) has been designed as a ligand programmed to promote the assembly of a molecular arrangement composed of three magnetically exchanged [NiCu] pairs, each exhibiting an = 1/2 spin. The latter are shown by EPR and magnetometry to be good qubit realizations and non-equivalent within the molecule in the solid state, as required for conditional quantum gates.